A Multivariate Analysis of Determinants of Profitability: Evidence from Selected Manufacturing Companies Listed on the Ghana Stock Exchange - Prempeh, Kwadwo Boateng; Sekyere, Allan McBright; Addy, Eric Kwame Amponsah (Journal of Accounting, Business and Finance Research, 2018)
This study seeks to examine the determinants of profitability of manufacturing companies in Ghana. The study covered the period 2005- 2015 using data gathered from five selected manufacturing companies listed on the Ghana Stock Exchange (GSE). The Study employed the Multivariate Regression Analysis Technique. Return on Assets, a measure of profitability, was used as the dependent variable whereas leverage, liquidity, firm size, tangibility, GDP, inflation and interest rate were used as the predictor variables. The findings of the study established that there is a statistically significant positive relationship between profitability, liquidity and firm size whereas leverage and interest rate show a statistically significant negative relationship with profitability. The macroeconomic environment in Ghana plays an essential role in the survival and profitability of manufacturing companies in Ghana as evident in the empirical results. Thus, it is vital that managers of the economy keep a close eye on the implications of their policies and their impact on the manufacturing sector in their attempt to grow the economy. Future research should consider the other equally important sectors of the economy. It should also include more variables such as taxation and regulation indicators, exchange rates, management quality and corporate governance to give room for a more robust result and findings.